Aina is Srikandi Matahari - Siti Sarah, Mohamad Rajimi (2017)
Kuantan,17 November – The recipient of Srikandi Matahari Award at the 12th UMP Convocation Ceremony, Sayyidatina Al Hurul Aina binti Alzahari, 24, does not stop her pursuit in study with only a Diploma in Computer Science at UMP but continues until she successfully graduated with a Bachelor Degree in Software Engineering from the sam university.